2023
DOI: 10.3390/w15091697
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Macroalgal Complexity and Allelochemicals Production in Invasive and Non-Invasive Macroalgae in the North-Western Adriatic Sea: Effect on the Associated Communities

Abstract: Highly diverse microphyto and meiobenthic communities are associated with large-sized marine macroalgae. Both morphological traits and allelochemical responses of macroalgae affect the composition of these communities, but the relative importance of these factors remains incompletely understood. In this study we investigated the microphytobenthic and meiobenthic communities associated with some native macroalgae and a non-indigenous species (Sargassum muticum) of the north-western Adriatic Sea. These seaweeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…A few studies have found that algal structural complexity had little influence on e.g. invertebrate species richness (Russo, 1990;Dijkstra et al, 2017) or abundance (Russo, 1990;Lenzo et al, 2023), while others have found that these relationships change temporarily. According to Da Rocha et al (2006), similar assemblages could be associated with structurally different macroalgae, but complexity still have an influence on the biology of the dominant groups of invertebrates.…”
Section: The Influence Of Individual Seaweed Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies have found that algal structural complexity had little influence on e.g. invertebrate species richness (Russo, 1990;Dijkstra et al, 2017) or abundance (Russo, 1990;Lenzo et al, 2023), while others have found that these relationships change temporarily. According to Da Rocha et al (2006), similar assemblages could be associated with structurally different macroalgae, but complexity still have an influence on the biology of the dominant groups of invertebrates.…”
Section: The Influence Of Individual Seaweed Featuresmentioning
confidence: 99%
“…Structural complexity has also been linked to a prominent group of red coralline algae, the Rhodoliths (Harvey and Bird, 2008;Stelzer et al, 2021;Neves and Costa, 2022). They create a porous habitat that enhances individual and bed physical complexity (Gabara et al, 2018, Cerqueira Veras et al, 2020, Goodsell et al (2004) 23 , Gunill (1982) 24 , Hacker and Steneck (1990) 25 , Harvey and Bird (2008) 26 , Hauser et al (2006) 27 , Hooper and Davenport (2006) 28 , Hughes (2010) 29 , Hull (1997) 30 , Karr (2011) 31 , Kelaher and Castilla (2005) 32 , Leite and Turra (2003) 33 , Lenzo et al (2023) 34 , Lilley and Schiel (2006) supporting significantly higher diversities than non-living beds or adjacent bare sediments (Robinson, 2015;Stelzer et al, 2021;Neves and Costa, 2022), or even some kelp beds (Schoenrock et al, 2018). Along with complexity, the depth (shallow or deep, in tropical or polar latitudes, respectively; Mikhaylova et al, 2019;Cerqueira Veras et al, 2020) and density of these beds also contribute to biodiversity.…”
Section: The Influence Of Individual Seaweed Featuresmentioning
confidence: 99%
See 1 more Smart Citation